2014
DOI: 10.21236/ada614547
|View full text |Cite
|
Sign up to set email alerts
|

Ignition of Nanoparticles by a Compact Camera Flash

Abstract: This report is published in the interest of scientific and technical information exchange, and its publication does not constitute the Government's approval or disapproval of its ideas or findings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
5
2

Year Published

2016
2016
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 8 publications
(11 reference statements)
2
5
2
Order By: Relevance
“…As already reported in the literature, the luminous energy value needed to trigger the ignition of SWCNT/Fe decreases with increasing Fe [711]. In this work, even if a different type of light source (i.e., CW Xe lamp instead of pulsed Xe lamp) has been used, a similar dependence between the ferrocene concentration and the minimum power needed for ignition was observed.…”
Section: Resultssupporting
confidence: 80%
See 1 more Smart Citation
“…As already reported in the literature, the luminous energy value needed to trigger the ignition of SWCNT/Fe decreases with increasing Fe [711]. In this work, even if a different type of light source (i.e., CW Xe lamp instead of pulsed Xe lamp) has been used, a similar dependence between the ferrocene concentration and the minimum power needed for ignition was observed.…”
Section: Resultssupporting
confidence: 80%
“…The reported results showed that a higher concentration of Fe reduces the minimum energy needed to trigger ignition [8–9]. The same results were also confirmed by other published research works [10–11]. …”
Section: Introductionsupporting
confidence: 79%
“…The discovery of the photo-ignition phenomenon of SWC-NTs or MWCNTs enriched with metal nano-particles presents considerable practical and commercial implications such as to attract significant interest from companies and international research organizations, first of all of those operating in the automotive and aeronautical field. In fact, the ignition phenomenon can be employed for triggering the combustion of solid, liquid and gaseous fuels (Badakhshan & Danczyk, 2014;Badakhshan, Danczyk, Wirth, & Pilon, 2011;Chehroudi, 2011Chehroudi, , 2012b. Furthermore, the photo-ignited nanoparticles allow to obtain a more distributed and homogeneous fuel combustion (Carlucci et al, 2014;Carlucci & Strafella, 2015;Johansson, 2007).…”
Section: Resultsmentioning
confidence: 99%
“…This experimental result is unexpected if compared with those found in literature where it is reported that a higher content of ferrocene facilitates the ignition. However, the photo-sensitive material used in our experimental tests is different from that used in literature; in this work, we have used MWCNTs-ferrocene mixtures while, in already published research works, samples of SWCNTs with 50% (by weight) Fe contents were tested (Badakhshan & Danczyk, 2014;Chehroudi, 2012b).…”
Section: Minimum Ignition Energy Found By Varying the Luminous Pulse mentioning
confidence: 99%
“…A quantitative analysis of the photo-ignition process of as-produced SWCNTs (with 50% Fe content), with varying pulse duration and wavelength ranges, was reported in [ 10 , 11 , 12 , 13 ]; the results highlighted that, regardless of the wavelength ranges of the incident light beam, the MIE (minimum ignition energy) values depend on the light pulse duration. In particular, a 30–35 mJ/pulse was required for igniting an uncompacted sample in steady air with a light pulse duration of 0.1 ms, whereas the 80–90 mJ/pulse had a pulse duration of 9 ms [ 10 ].…”
Section: Introductionmentioning
confidence: 99%